Development of Pluralist and Multicultural Approaches In PAI Learning: A Conceptual Model For Strengthening Students' Inclusivity Competencies - Nurhartanto, Armin; Anwar, Sholihul; Sukisno, Sukisno (Multicultural Islamic Education Review, 2024)
In a culturally and religiously diverse society like Indonesia, Islamic Religious Education (PAI) must promote values of inclusivity, tolerance, and respect. This study aims to develop a conceptual model that integrates pluralist and multicultural approaches into PAI learning to enhance students’ inclusivity competencies. Using a qualitative methodology, the research adopts a systematic literature review analyzing primary and secondary sources, including academic books, journal articles, and policy documents. Content analysis was employed to extract key themes related to the implementation of pluralism and multiculturalism in Islamic education. The findings indicate that an effective integration requires the alignment of curriculum design, teaching methods, teacher roles, learning materials, and evaluation systems with inclusive values. It emphasizes that multicultural education focuses on cultural and ethnic diversity, while pluralist education addresses religious pluralism and interfaith understanding. Both approaches are complementary in creating an inclusive and peaceful educational environment. The study concludes that the conceptual model can serve as a foundation for reforming PAI by fostering tolerance, empathy, and cooperation among learners. It also suggests that further empirical research and implementation trials are needed to test the model in practice.